6x+3=7+4x

Simple and best practice solution for 6x+3=7+4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+3=7+4x equation:


Simplifying
6x + 3 = 7 + 4x

Reorder the terms:
3 + 6x = 7 + 4x

Solving
3 + 6x = 7 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
3 + 6x + -4x = 7 + 4x + -4x

Combine like terms: 6x + -4x = 2x
3 + 2x = 7 + 4x + -4x

Combine like terms: 4x + -4x = 0
3 + 2x = 7 + 0
3 + 2x = 7

Add '-3' to each side of the equation.
3 + -3 + 2x = 7 + -3

Combine like terms: 3 + -3 = 0
0 + 2x = 7 + -3
2x = 7 + -3

Combine like terms: 7 + -3 = 4
2x = 4

Divide each side by '2'.
x = 2

Simplifying
x = 2

See similar equations:

| x+4=225 | | 6*(4x-3)+20x-24x^2=14 | | x+6=258 | | 5x-4=5x+4 | | 2=3 xx1 | | ax+3=c | | 3x+5y=200.4 | | 4-3a+4=0 | | 7x-3(x+2)=4x+3 | | 2(x+5)=4x-(2x-10) | | 6x(4x-3)+20x-24x^2=14 | | 6(2-3x)=5(x+4) | | (a-b)(2a^3-ab+3b^2)=0 | | 11.5(2x-6)=4(3.5x+12) | | 3.5=2.5d+5 | | y^2+27y=0 | | x^5+6x+17=0 | | 2/3x-3/2x=1/12 | | 1/8+2/9 | | (2x+5)(x-9)= | | P=r+s-p | | x^2+36x+27= | | 4a^2-12a-7=0 | | 6-2*7=4x-6x-3 | | 10y+(3y+11)=180 | | 18-6a=12 | | 0=x+7-32 | | 35.00+0.75x=20 | | 5m+6n=64 | | (4+7i)+(-3+5i)=1+12i | | 2a+4b=46 | | 1.25x=25 |

Equations solver categories